Compacts formation process - Yu. V. Podkolzin; A. V. Avlasenko; I. M. Peshkhoev (Advanced Engineering Research, 2018)
Introduction. Biomass is used as foodstuff, for feed making, and for energy production. This is a dispersed material characterized by high porosity and low density, which is poorly adapted for use. Therefore, to improve its processability, biomass is subjected to compaction to shape compacts (feed wafers, granules, etc.). Materials and Methods. The process of packing biomass in compacts is considered. It is shown that the resistance of dispersed materials to compaction, which includes biomass, is determined by the structural and mechanical properties of the material compacted – structural strength, internal friction, connectivity pressure, strength of the material particles, and bond strength between particles. Theoretical studies have determined the relationships between all the characteristics of dry biomass which form the basis for calculating machines for shaping biomass in compacts. Research Results. A technique is developed that allows determining the critical parameters of the press with ring dies due to the requirements for the compacts and structural and mechanical properties of the material compacted. The technique is recommended for designing machines providing the formation of biomass in compacts with specified properties. Discussion andConclusions. The obtained patterns can be used under designing presses for the production of tailored compacts.